How do European patients feel about the listening skills of primary care physicians? Results from the EUprimecare Project - Sánchez Piedra, Carlos Alberto; García-Pérez, Sonia; Prado-Galbarro, Francisco Javier; Sarría-Santamera, Antonio (Farmeconomia. Health Economics and Therapeutic Pathways, 2014)
OBJECTIVE: EUprimecare is a study funded by the 7th Framework Programme of the European Union aimed at analyzing the quality of the different models of primary care (PC) in Europe. The objective of this study was to describe and analyze the determinants associated with patient satisfaction with the listening skills of their PC physicians. METHODS: Telephone population survey in each EUprimecare consortium countries (Germany, Spain, Estonia, Finland, Hungary, Italy and Lithuania) among PC users. The questionnaire included sociodemographic variables, health status, use and satisfaction with PC services. The survey was conducted in 3020 patients. It was developed descriptive analysis, bivariate correlations and ordinal regression model to study the direct relation between levels of satisfaction and the explanatory variables on demographics, state and health services for patients. We show the regression coefficients (β) with 95% confidence interval and statistical significance associated. RESULTS: We found significant relation between the level of satisfaction and age (β = 0.016), visits to specialist (β = ‑0.040), having a general practitioner (GP) (β = 0.619), having a chronic disease (β = 0.255), measuring weight, cholesterol and blood pressure (β = 0.650), countries (β1 Estonia= 0.938; β2 Germany = 0.469; β3 Lithuania = 0.483; β5 Italy = 0.544 and β6 Hungary = 1.010) and a better perception of health status (β = 0.388). Specialist visits have a negative influence with the higher degree of satisfaction. CONCLUSIONS: Overall, the results indicate some areas that may be related to greater doctor‑patient satisfaction. Different factors are converging to explain satisfaction with listening skills.